The Asian financial crisis : crisis, reform, and recovery - Sharma, Shalendra D., 1958- (Manchester University Press, 2003)
The Asian financial crisis of 1997-98 shook the global economy. What began as a localized currency crisis soon engulfed the entire Asian region. What went wrong and how did the Asian economies, long considered "miracles", respond? This book provides answers to this and other questions.